Comparison of the Concentrations of Lidocaine in Different Body Fluids/Tissues after Subarachnoid Space and Intravenous Administration of a Lethal Dose of Lidocaine - Nan Zhang; JunHong Sun; Zhiwen Wei; Wenyan He; Guohua Jin; Xiaohong Zhang; Pengxiang Gao; Longmei Wang; Keming Yun (Wolters Kluwer Medknow Publications, 2015)
The objective of the study was to compare the concentration of lidocaine in different body fluids/tissues after subarachnoid space and intravenous administrations of a lethal dose of lidocaine. Totally 18 dogs were used in the experiment. Six dogs were given subarachnoid anesthesia, another were given an intravenous injection of a dose of 75 mg/kg weight of lidocaine hydrochloride in 5 min and the last 6 dogs were used as the blank control dogs and given a subarachnoid space injection or a femoral artery injection of the same volume of sodium chloride. As soon as its vital signs disappeared, each dog was dissected and the specimen, such as brain, cerebrospinal fluid (CSF) in lateral ventricle, CSF in subarachnoid space, spinal cord (cervical spinal cord, thoracic spinal cord, lumbar spinal cord, and waist spinal cord), heart, lung, liver, spleen, kidney, bile, urine, heart blood, peripheral blood, muscle in injection location, and muscle in no injection location, were collected for analysis of lidocaine immediately. Analysis was performed with gas chromatography-mass spectrometry (GC-MS). From the maximum to the minimum, the order of lidocaine concentration detected in the subarachnoid space-administered dogs was as follows: CSF in subarachnoid space, waist spinal cord, thoracic spinal cord, CSF in lateral ventricle, lumbar spinal cord, cervical spinal cord, lung, kidney, muscle in injection location, heart, brain, spleen, heart blood, liver, peripheral blood, bile, muscle in no injection location, and urine. The order of lidocaine concentration detected in the intravenously administered dogs was as followed: Kidney, heart, lung, spleen, brain, liver, peripheral blood, bile, heart blood, cervical spinal cord, thoracic spinal cord, muscle in injection location, lumbar spinal cord, muscle in no injection location, CSF in subarachnoid space, urine, and CSF in lateral ventricle. The maximum concentration of lidocaine was detected in the subarachnoid space CSF of subarachnoid space-administered dead dogs, while in intravenously injected dead dogs, the maximum concentration of lidocaine was detected in the kidney. Our study provides some useful data for the forensic identification of epidural anesthesia accidents to decide the way the lidocaine enters the body.